Efektifitas Kombinasi Zat Pengatur Tumbuh (ZPT) dan Sumber Eksplan pada Kultur Jaringan Tanaman Kakao (Theobroma cacao L) dan lada (Piper nigrum L): Effectiveness of the Combination Plant Growth Regulator (PGR) and Explant in Plant Tissue Cultures of Cacao (Theobroma cacao L) and Pepper (Piper nigrum L) - Muktirianur; Yudi; Regina Selina Putri; Khairunnisa Azizah Salsabila (Universitas Widya Gama Mahakam, 2023)
The plantation sector is one of the largest contributors to Indonesia's foreign exchange, this can be seen from the value of exports that have been contributed by the plantation sector. Cocoa (Theobroma cacao L) and pepper (Piper nigrum L) are plantation crops that contribute a lot to the country's foreign exchange. East Kalimantan is one of the areas that has a climate that supports the growth of cocoa and pepper plants, but their production is still very minimal. East Kalimantan has a large enough marginal land, marginal land is land that has environmental conditions that are less fertile or difficult to cultivate conventionally. The assembly of new varieties through tissue culture techniques makes it possible to produce many new plants in a short time, so that these new varieties can be used to increase cocoa and pepper production in East Kalimantan. This study aims to obtain the right combination of PGR and explant for the utilization of tissue culture on cocoa and pepper plants in assembling new varieties of cocoa and pepper plants in vitro. This research consists of two experiments. The first experiment was optimizing the explants and PGR combinations used for cocoa plants and the second experiment was optimizing the explants and PGR combinations used for pepper plants. The design used in this study was complete random design Factorial with 2 factors and 5 replications. The first factor used in this research is the source of the explants. For cocoa plants in the form of Staminoid (K1) and Petal (K2). As for pepper plants, namely leaves (L1) and shoots (L2). The second factor for each experiment was the combination of PGR in tissue culture media, namely solid WPM media with the addition 1 mg L-1 2,4D + 0,5 mg L-1 BAP + 30 g L-1 sucrose (W1) and Solid WPM with the addition of ZPT 1 mg L-1 NAA + 7 mg L-1 Kinetin + 30 g L-1 sucrose (W2). The use of WPM + 1 mg L-1 2,4D + 0,5 mg L-1 BAP (W1) media on both cocoa and pepper plants was able to induce callus. Whereas on WPM + 1 mg L-1 NAA + 7 mg L-1 Kinetin (W2) media it was able to form shoots. For the best source of explants used for the assembly process or propagation of cocoa and pepper plants, explants of cacao staminoid (K1) and pepper leaves (L1) can be used.